RETRACTED: Éclaircissement to Understand Consumers’ Decision-Making Psyche and Gender Effects, a Fuzzy Set Qualitative Comparative Analysis - Mustafa, Sohaib; Sohail, Muhammad Tayyab; Alroobaea, Roobaea; Rubaiee, Saeed; Anas, A.; Othman, Asem Majed; Nawaz, Muhammad (Frontiers in Psychology, 2022)
Consumers’ decision-making is complex and diverse in terms of gender. Different social, psychological, and economic factors mould the decision-making preferences of consumers. Most researchers used a variance-based approach to explain consumer decision-making that assumes symmetric relationship between variables. We have collected data from 468 smartwatch users and applied a fuzzy set qualitative comparative analysis (fsQCA) to explain and compare male and female consumers' decision-making complexity. fsQCA assumes that an asymmetric relationship between variables can exist in the real world, and different combinations of variables can lead to the same output. Results explain that different variables have a core and secondary level of impact on consumer decision-making. Hence, we can not claim that certain factors are significant or insignificant for decision-making. Fsqca results revealed that cost value, performance expectancy, and social influence play a key role in consumers' buying decisions. This study has contributed to the existing literature by explaining consumer decision-making by applying configuration and complexity theories and identifying unique solutions for both genders. A major contribution to theoretical literature was also made by this research, which revealed the complexity of consumer purchasing decisions made for new products.